Optimizing Online Dispute Resolution (ODR) in Joint Property Dispute Resolution After Divorce in Indonesia - Kamaluddin Pane (Program Pascasarjana UIN Sumatera Utara Medan, 2026)
The settlement of joint property disputes after divorce in Indonesia is generally still pursued through litigation mechanisms in court, which in practice often takes a relatively long time, high costs, and has the potential to worsen the relationship between the parties. The development of information technology has given birth to Online Dispute Resolution (ODR) as an alternative dispute resolution that offers a faster, more efficient, and more flexible process. However, the implementation of ODR in resolving joint property disputes in Indonesia still faces obstacles in the form of the absence of legal arrangements that specifically regulate the mechanisms, procedures, and legal force of online dispute resolution. This study aims to analyze the urgency of the implementation of ODR in resolving joint property disputes after divorce and examine efforts to optimize its application in a positive Indonesian legal perspective. This research uses normative legal research methods with a statutory approach and a conceptual approach. Legal materials are obtained through literature studies consisting of primary, secondary, and tertiary legal materials, then analyzed qualitatively by descriptive-analytical methods. The results of the study show that although Indonesia's positive law has not comprehensively regulated ODR, the provisions in Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution, Law Number 11 of 2008 concerning Information and Electronic Transactions and its amendments, and Supreme Court Regulation Number 1 of 2016 concerning Mediation Procedures in Court provide a normative basis for the use of technology in dispute resolution. Optimizing ODR requires harmonizing regulations, strengthening the capacity of mediators, and providing digital platforms that ensure legal certainty, data security, and protection of the rights of parties. Thus, ODR has the potential to become a complementary mechanism in resolving joint property disputes that is able to realize the principle of simplicity, fast, low-cost, and expand access to justice.